(untitled) (Al-Academy, 2021)
The tagged research (realism in the Paintings of Iraqi Kurdistan artists, “a study of expression methods”) dealt with realism in an objective way, as well as the complexity of its concepts through its formations and formations. On realism and its historical dimension in concept and meaning, as for the second chapter, the research was focused on the methods of expression in painting, while the third chapter was concerned with the procedural applications of realistic methods of expression in the drawings of Iraqi Kurdistan, and according to these axes and to achieve the goal of the research, a number of Among the results are:1- Realism documented the life of the Kurdish society in line with the developments of the era, as the style witnessed the feature of modernization through balancing between form and content and due to the effects of the political situation, as it was subject to philosophical vision, dialectical ideas and concepts.2- Realism achieved in its critical dimension a discovery of artistic insight and dreamy fantasy about artworks that dealt with symbol, heroism and legend